El anonimato de la donación de gametos. ¿hay que mejorar la situación actual? - Margarita Boladeras-Cucurella (Universitat de Barcelona, 2023)
The anonymity of gamete donation is the subject of harsh criticism from the people born by assisted reproduction techniques (ART) with donor gametes or embryos, both in Spain and in other countries. The text provides information on this situation and on the various laws in different countries, as well as the ethical orientation of the principles to be respected. Many countries have legislated for years on the non-anonymity of ART donors and the Council of Europe approved a recommendation in 2019 advising to follow this model. goal. To point out situations that should be avoided, present arguments and actions to overcome them. method. Narration of personal situations of legal distress, ethical and jurisprudential analysis of the same, and proposals for action to avoid such situations. conclusions. Need for legislative changes in many countries, including Spain, to protect the right to know the origins of those born by gamete donation.